The ageing of Croatian population - Murgić, Jure (Array, 2009)
Abstract: With a share of people older than 65 years of 16.64 per cent in total population, Croatia is considered a very old country regarding it’s population. This percentage is one of the highest in already old Europe. Demographic projections reveal a further increase of share of people older than 65 years in future. There are many causes of this condition. This fact carries negative economic and healt care implications which burden Croatia. Many administrative reforms are necessary to resolve this issue and to avoid economy problems and intergenerational conflicts